Increasing Interest In Reading Through the School Literacy Movement Program in Class IV State Elementary School 27 Pontianak Timur - Madeten, Sisilya Saman; Kurniawan, Kurniawan; Khotimah, Siti Aulia; Azzahra, Nurieska Fadia; Gapo, Cristianus William (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
This study aims to determine the implementation of GLS in Class IV State Elementary School Negeri 27 East Pontianak through the application of GLS principles and its impact on students' interest in reading. The research method used was descriptive qualitative with data collection techniques of observation, interview and documentation. The results showed that the implementation of GLS at Class IV State Elementary School Negeri 27 East Pontianak was carried out through reading habit 15 minutes before lessons, providing reading materials at school, teachers giving reading examples, and students forming reading study groups. However, the utilization of technology in GLS has not been maximized. The positive impact of GLS on students' reading interest is characterized by an increase in the number of library visits and students actively reading outside of class hours. Lack of facilities such as a narrow reading room is an obstacle. Based on the results of the study, strategies are needed to improve the implementation of GLS through the utilization of technology and improvement of supporting facilities. This aims to realize a sustainable literacy culture at Class IV State Elementary School Negeri 27 East Pontianak.